Spatial and temporal dynamics of shifting cultivation in the middle-Amazonas river: Expansion and intensification - Jakovac, Catarina Conte; Dutrieux, Lo?c Paul; Siti, Latifah; Pena-Claros, Marielos; Bongers, Frans (PLoS ONE, 2017)
Shifting cultivation is the main land-use system transforming landscapes in riverine Amazonia. Increased concentration of the human population around villages and increasing market integration during the last decades may be causing agricultural intensification. Studies have shown that agricultural intensification, i.e. higher number of swidden-fallow cycles and shorter fallow periods, reduces crop productivity of swiddens and the regrowth capacity of fallows, undermining the resilience of the shifting cultivation system as a whole. We investigated the temporal and spatial dynamics of shifting cultivation in Brazilian Amazonia to test the hypotheses that (i) agriculture has become more intensive over time, and (ii) patterns of land-use intensity are related to land accessibility and human population density. We applied a breakpoint-detection algorithm to Landsat time-series spanning three decades (1984–2015) and retrieved the temporal dynamics of shifting cultivation fields, which go through alternating phases of crop production (swidden) and secondary forest regrowth (fallow). We found that fallow-period length has decreased from 6.4 to 5.1 years on average, and that expansion over old-growth forest has slowed down over time. Shorter fallow periods and higher frequency of slash and burn cycles are practiced closer to residences and around larger villages. Our results indicate that shifting cultivation in riverine Amazonia has gone through a process of agricultural intensification in the past three decades. The resulting landscape is predominantly covered by young secondary forests (≤ 12 yrs old), and 20% of it have gone through intensive use. Reversing this trend and avoiding the negative consequences of agricultural intensification requires land use planning that accounts for the constraints of land use in riverine areas. © 2017 Jakovac et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.
Keywords: Active Shifting Cultivation Landscape; Agricultural Intensification; Agricultural Management; Agricultural Procedures; Agriculture; Algorithm; Breakpoint Detection Algorithm; Controlled Study; Crop Production; Size Effect; Environmental Aspects And Related Phenomena; Environmental Parameters; Forestry; Land Accessibility; Land Use; Land Use Planning; Landscape; Middle Amazon River; Population Density; Probability; River; Secondary Forest Regrowth; Shifting Cultivation; Shorter Fallow Period; Spatial Dynamics; Survival Rate; Temporal Dynamics; Time Series Analysis; Environmental Protection; Forest; Growth, Development And Aging; Human; River; Tree; Agriculture; Conservation Of Natural Resources; Forests; Humans; Rivers; Trees